The versatile utility of cysteine as a target for cancer treatment - Min, Jin-Young; Chun, Kyung-Soo; Kim, Do-Hee (Frontiers in Oncology, 2023)
Cysteine is a sulfhydryl-containing proteinogenic amino acid essential for the human body. It is also utilized in various metabolic pathways, including the regulation of reduced glutathione (GSH) as a major endogenous antioxidant molecule and the generation of sulfur-containing biomolecules. In addition, cysteine residues in proteins have the reactive thiol (-SH) group, which can undergo various post-translational modifications. Moreover, endogenous or exogenous electrophilic molecules can be covalently modified with cysteine, resulting in altered cellular states and functions. Some pharmacological agents that exploit the modification of cysteine residues present in many intracellular proteins affect the biological activity, thus exerting their drug effects. Therefore, in cancer metabolism and cancer cell survival, cysteine plays an essential role for redox regulation in cellular status and protein function. In this review, we summarize the diverse regulatory mechanisms of free- or bound cysteine in cancer. This review will provide the foundation for further understanding cysteine in tumor biology and developing novel effective cancer therapies.